Eliminating Contamination in Umbilical Cord Blood Culture Sampling for Early-Onset Neonatal Sepsis - Quinones Cardona, Vilmaris; Lowery, Vanessa; Cooperberg, David; Anday, Endla K.; Carey, Alison J. (Frontiers in Pediatrics, 2021)
Introduction Despite the advantages of umbilical cord blood culture (UCBC) use for diagnosis of early onset sepsis, contamination rates have deterred neonatologists from its widespread use. We aimed to implement UCBC collection in a level III neonatal intensive care unit (NICU) and apply quality improvement (QI) methods to reduce contamination in the diagnosis of early onset sepsis (EOS). Methods Single-center implementation study utilizing quality improvement methodology to achieve 0% contamination rate in UCBC samples using the Plan-Do-Study-Act (PDSA) model for improvement. UCBC was obtained in conjunction with peripheral blood cultures (PBC) in neonates admitted to the NICU due to maternal chorioamnionitis. Maternal and neonatal characteristics between clinical sepsis and asymptomatic groups were compared. Process, outcome, and balancing measures were monitored. Results Eighty-two UCBC samples were collected in addition to peripheral blood culture (PBC) from neonates admitted due to maternal chorioamnionitis. Ten (12%) neonates had a diagnosis of clinical sepsis. All PBCs were negative and 5 UCBCs were positive in the study period. After 2 PDSA cycles, there was special cause variation with improvement in the percent of contaminated samples from 7.3% to 0%. There was no change in antibiotic duration among asymptomatic neonates. Conclusions Implementation of UCBC for the diagnosis of EOS in term infants is feasible and contamination can be minimized with the implementation of a core team of trained providers and a proper sterile technique without increasing antibiotic duration.